ANALYSIS OF FACTORS AFFECTING BUDGET ABSORPTION - Nur Hidayati; Ananda Frisca Ayu Rosida; Dini Ayunda Sari; Fatchur Rohman (JASS (Journal of Accounting for Sustainable Society), 2024)
This research is intended to examine the impact of budget planning, record administration, and human resource competency on budget absorption in state vocational high schools in Jepara. A total of 45 respondents who served in positions related to the budget, including commitment making officials, technical implementation officials for activities, budget user officials, payment order signing officials, and expenditure treasurers at state vocational high schools in Jepara were taken as research samples. The results of multiple linear regression analysis show that budget planning has a positive impact on budget absorption, administrative records also have a positive impact on budget absorption, and human resource competence has a positive impact on budget absorption